Family constellations in contemporary Ibero-American and Slavic literatures: historical imaginary, transnationality, narrative form - Artwińska, Anna; Calderón Villarino, Ángela; Welge, Jobst (De Gruyter, 2024)
This volume examines Ibero-American as well as Slavic literatures of the 21st century and studies how historical imaginaries in family narratives are functionalized for both individual and collective and (post-)national identities. The analysis proceeds along three conceptual axes. What these narratives have in common is that they construct specific constellations of the historical imagination and of family, whereby ‘family’ is here conceived not so much as an organic micro-unity, but rather as changing, multiple relations between individual members, godparents, first- and second-degree relatives, non-blood-related family members, present and absent members, adopted children, etc. Furthermore, these novels are often grounded in trans-generational memories. They are written by members of a generation that, as a rule, did not directly experience these historical events. It is also significant that these narratives are no longer conceived as representing national identities, but paradigmatically speak for a collective that defines itself in regional, ethnic, religious or ideological terms. It seems, therefore, that these narratives of family constellations are in need of more flexible typological rubrics and interpretive frameworks. Intended as a sustained comparative study of these family narratives, this volume is a contribution in understanding how historical caesura, experiences, and their literary representation work on the self-understanding of the present